Sedentary Lifestyle And Screen Time On Nutritional Status - MT Simangunsong, David (Jurnal EduHealth, 2022)
Nutritional status on teenager is a matter important thing to do is known by every individual so can anticipate And prevent happening nutrition not enough nor nutrition more. During this pandemic period, Covid-19 not only impacted income, but also improved nutritional status for teenagers in Indonesia. this is to support the teenager For own sedentary lifestyle and screen team no health related with Body Mass Index (BMI) enhancement. The goals of this research are to discover the relationship between sedentary lifestyle and screen time with nutritional status of grade X students at SMKN 2 North Rantau during the covid-19 pandemic. This type of study is analytic observational with a cross-sectional design. This research was conducted from August to September 2022. Data capture was only done one time and using primary data from the results of a class X student questionnaire at SMKN 2 North Rantau. The amount of sample obtained was as many as 85 students with the technique of taking samples of clusters sampling . On the sedentary lifestyle connection where the results of the chi-square test analysis with p value 0.718 (p>0.05), there was no significant relationship between sedentary lifestyle and nutritional status on students at SMKN 2 North Rantau. On connection screen time test analysis chi-square with p-value 0.852 (p>0.05), there was no significant relationship between physical activity and nutritional status on students at SMKN 2 North Rantau. Mark significant between sedentary lifestyle and screen time on nutritional status value of r>0.05 (r<0.05) which means there is no meaningful relationship between sedentary lifestyle and duration of screen time on nutritional status student class X at SMKN 2 North Rantau during the Covid period -19 pandemics .